Mathematics students’ writing skills: Assesment in higher education with Rasch model - Riza Agustiani; Hartatiana Hartatiana; Ambarsari Kusuma Wardani (Universitas Islam Negeri Maulana Malik Ibrahim, 2018)
The aim of this research is to describe the students’ scientific writing skills of mathematics education. This research is descriptive qualitative research. Research subject is choosen by using purposive sampling technique. Research subject is choosen based on variety of batch, grade point average (GPA) dan Thesis Processing Duration (TPD). Data collection techniques in this research are document studies (documentation methods) and interviews. The document study was carried out by 2 researchers (chairman and researcher members) and 2 other lecturers of Mathematics Education Study Program to obtain data about writing scientific work for research subjects. The interview was conducted after the results of the first data analysis were obtained as confirmation media and deeper exploration of the profile of the research subjects. This study provides an overview of the carrying capacity of the GPA characteristics, the value of Indonesian Language, the value of Research Methods, and TPD. The four characteristics do not significantly support the students’ cientific writing skills of the mathematics education study program.